The more things change, the more they stay the same: the Queensland Police Service as a model for sustainable policing reform - Alpert, Geoffrey P. (International journal of comparative and applied criminal justice, 2021)
Police departments are consistently challenged to serve their communities by reducing misconduct and being held accountable. In the United States, policing reform is best described as déjà vu or Groundhog Day, with high-profile groups organising every few years to list the same recommendations for improving the police. Additionally, reform suggestions are too often countered by the comment, “we have always done it this way.” By stark contrast, through the Fitzgerald Inquiry and the work of scholars such as David Bayley, the Queensland Police Service stands as a model for creating sustainable change in policing. In this paper, we compare the experiences of the Queensland Police Service with attempts at reform in the United States to suggest a path forward for reforming policing in the US.